The ethics of educational leadership - Rebore, Ronald W. (Upper Saddle River, New Jersey : Pearson Education, 2014)
This book presents a foundations approach to educational ethics which applies theory to practice using case studies, exercises, discussion statements, and questions. Through the ethical ideas and notions of 20 philosophers and psychologists-from the Ancient Historical Period, the Modern Period, and the Contemporary Historical Period. Through this presentation, tomorrow's educational leaders can evaluate the philosophical ideas of others and use what they discover to develop their own way of approaching their leadership responsibilities. In this new edition, five new chapters deal with the legal aspect of ethics, and how communication creates the milieu within which ethics is practiced.
Part One. The Ethical administrator -- Part Two. The Ethical practice of educational leadership -- Chapter Three. Equity in ethical educational leadership -- Part Four. Human communication and the ethics of educational leadership.
Includes bibliographical references and index.
Keywords: EDUCATIONAL LEADERSHIP